Golgi-Resident GTPase Rab30 Promotes the Biogenesis of Pathogen-Containing Autophagosomes - Oda, Seiichiro (PLoS One, 2016)
Autophagy acts as a host-defense system against pathogenic microorganisms such as Group A Streptococcus (GAS). Autophagy is a membrane-mediated degradation system that is regulated by intracellular membrane trafficking regulators, including small GTPase Rab proteins. Here, we identified Rab30 as a novel regulator of GAS-containing autophagosome-like vacuoles (GcAVs). We found that Rab30, a Golgi-resident Rab, was recruited to GcAVs in response to autophagy induction by GAS infection in epithelial cells. Rab30 recruitment was dependent upon its GTPase activity. In addition, the knockdown of Rab30 expression significantly reduced GcAV formation efficiency and impaired intracellular GAS degradation. Rab30 normally functions to maintain the structural integrity of the Golgi complex, but GcAV formation occurred even when the Golgi apparatus was disrupted. Although Rab30 also colocalized with a starvation-induced autophagosome, Rab30 was not required for autophagosome formation during starvation. These results suggest that Rab30 mediates autophagy against GAS independently of its normal cellular role in the structural maintenance of the Golgi apparatus, and autophagosome biogenesis during bacterial infection involves specific Rab GTPases.